The Influence of Leadership Humility, Work Engagement, and Monetary Rewards on Employee Creativity with Knowledge Sharing as a Mediating Variable (A Study at PT Kimia Farma Trading & Distribution Madiun) - Very Bangun Sulistyo; Ahadiati Rohmatiah; Mintarti Indartini (International Journal of Business and Quality Research, 2026)
One of the key factors of marketing success at PT Kimia Farma Trading & Distribution Madiun, which operates in the distribution and trading of health products, is employee creativity. Considering the importance of employee creativity, companies must be able to understand the various factors that encourage employee creativity. This study aims to empirically prove the influence of leadership humility, work engagement, and monetary rewards on employee creativity through the mediation of knowledge sharing among employees of PT Kimia Farma Trading & Distribution Madiun. The study population was all 67 employees of PT Kimia Farma Trading & Distribution Madiun in 2026. The entire population was sampled, so the sampling technique used was total sampling. The research instrument used a questionnaire. The data analysis technique used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the study show that: 1) Leadership humility, work engagement, and monetary rewards do not directly influence employee creativity, 2) Leadership humility, work engagement, and monetary rewards directly influence knowledge sharing, 3) Knowledge sharing directly influences employee creativity, 4) Knowledge sharing mediates the influence of leadership humility and monetary rewards on employee creativity with fully mediated, 5) Knowledge sharing does not mediate the influence of work engagement on employee creativity among employees of PT Kimia Farma Trading & Distribution Madiun.